Design and development of an affordable customized EVA shoes for Individuals suffering from a non-flexible “Metatarsus Adductus” (Cuestiones de Fisioterapia, 2025)
In this work, an affordable modified Ethylene-vinyl acetate (EVA) shoe was designed and developed for the persons suffering from “Metatarsus Adductus” foot deformity. The effects of developed shoes on the subjects gait parameters (i.e., speed, stride length, step length, double support time, and hip, knee, and ankle movement) were analyzed. The study involved measuring the subjects foot morphology, manufacturing custom EVA shoes, and presenting factors that helped reduce the cost of custom-made shoes while enhancing the subjects comfort. The stiffness of the lateral portion of the sole was modified to balance load distribution in the plantar region. Additionally, an inverted heel provision was incorporated to address excessive pronation moments. Gait analysis was conducted using a markerless pose estimation algorithm in different shod conditions (i.e., regular closed-toe shoes, open-toe slippers, and the modified/customized EVA shoes). The results were statistically analyzed using a two-sample t-test, and Bland-Altman analysis was performed to identify fixed and proportional biases in the dataset. To validate test reliability, the Intraclass Correlation Coefficient (ICC (3,1)) (Two-way mixed effects, single rater) was also calculated. The results confirmed that the modified EVA footwear positively impacted the subjects ambulatory movement (e.g., increased step length, stride length, and range of motion), which was further supported by the subjects feedback. This work provides valuable insights into low-cost manufacturing of both regular and customized footwear.